Resistance training and cardiac hypertrophy: unravelling the training effect - Haykowsky, M. J.; Dressendorfer, R.; Taylor, D.; Mandic, S.; Humen, D. (Sports Medicine, 2002)
Resistance training (RT) is a popular method of conditioning to enhance sport performance as well as an effective form of exercise to attenuate the age-mediated decline in muscle strength and mass. Although the benefits of RT on skeletal muscle morphology and function are well established, its effect on left ventricular (LV) morphology remains equivocal. Some investigations have found that RT is associated with an obligatory increase in LV wall thickness and mass with minimal alteration in LV internal cavity dimension, an effect called concentric hypertrophy. However, others report that short- (<5 years) to long-term (>18 years) RT does not alter LV morphology, arguing that concentric hypertrophy is not an obligatory adaptation secondary to this form of exertion. This disparity between studies on whether RT consistently results in cardiac hypertrophy could be caused by: (i) acute cardiopulmonary mechanisms that minimise the increase in transmural pressure (i.e. ventricular pressure minus intrathoracic pressure) and LV wall stress during exercise; (ii) the underlying use of anabolic steroids by the athletes; or (iii) the specific type of RT performed. We propose that when LV geometry is altered after RT, the pattern is usually concentric hypertrophy in Olympic weightlifters. However, the pattern of eccentric hypertrophy (increased LV mass secondary to an increase in diastolic internal cavity dimension and wall thickness) is not uncommon in bodybuilders. Of particular interest, nearly 40% of all RT athletes have normal LV geometry, and these athletes are typically powerlifters. RT athletes who use anabolic steroids have been shown to have significantly higher LV mass compared with drug-free sport-matched athletes. This brief review will sort out some of the factors that may affect the acute and chronic outcome of RT on LV morphology. In addition, a conceptual framework is offered to help explain why cardiac hypertrophy is not always found in RT athletes.